Beam Column and Footings Connection of Simple Prefab Housing. (2015) - Limanto, Sentosa; Suwono, Johanes Indrojono
Abstract: To meet the urgent need for transmigration and to displacements due to natural disasters, prefab housing system is required for fast construction. This study proposed a joint system to connect footings, concrete column / pedestal, and the tie beams. From four types of connections two were deemed appropriate. A prototype, 2×2×2 m, was built for this purpose and tested for the reliability of the connections. It appears that the connection could resist a horizontal force of 10% the column load and able to withstand a differential settlement of 2 cm. Erection with simple tools to assemble the components of the prototype only needs less than 6 hours by three laborers. Factory made components will speed up the installation.